BIOMEDICAL PROPERTIES AND APPLICATIONS OF CHITOSAN DERIVATIVES - Yoqubjonova, Madinabonu; Boymirzaev , Azamat (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
In this era, there is a global concern in the use of bioactive molecules such as chitosan in the ﬁeld of antimicrobial and antioxidant beneﬁts. Because of its biodegradability, biological compatibility, antimicrobial, antioxidants activity, and high safety, chitosan may be applied to in a large number of applications. It could exist in many forms, such as ﬁbers, gels, ﬁlms, sponges, nanoparticles, and beads. Additionally, further uses for chitosan and its byproducts, including wound healing products, wastewater treatment, and cosmetics, have also been highlighted. This analysis aligns with our earlier review that presented data collected through 2023 and compiles the most recent results regarding the antibacterial, antifungal, and antioxidant properties of chitosan derivatives.